Performance Improvements of Selective Emitters by Laser Openings on Large-Area Multicrystalline Si Solar Cells - Sheng-Shih Wang; Jyh-Jier Ho; Jia-Jhe Liou; Jia-Show Ho; Wei-Chih Hsu; Wen-Haw Lu; Song-Yeu Tsai; Hsien-Seng Hung; Kang L. Wang (International Journal of Photoenergy)
This study focuses on the laser opening technique used to form a selective emitter (SE) structure on multicrystalline silicon (mc-Si). This technique can be used in the large-area (156 × 156 mm2) solar cells. SE process of this investigation was performed using 3 samples SE1–SE3. Laser fluences can vary in range of 2–5 J/cm2. The optimal conversion efficiency of 15.95% is obtained with the SE3 (2 J/cm2 fluence) after laser opening with optimization of heavy and light dopant, which yields a gain of 0.48%abs compared with that of a reference cell (without fluence). In addition, this optimal SE3 cell displays improved characteristics compared with other cells with a higher average value of external quantum efficiency (EQEavg = 68.6%) and a lower average value of power loss (Ploss = 2.33 mW/cm2). For the fabrication of solar cells, the laser opening process comprises fewer steps than traditional photolithography does. Furthermore, the laser opening process decreases consumption of chemical materials; therefore, the laser opening process decreases both time and cost. Therefore, SE process is simple, cheap, and suitable for commercialization. Moreover, the prominent features of the process render it effective means to promote overall performance in the photovoltaic industry.